Experiences of nurse managers and practitioners on implementation of an evidence-based practice intervention - Catherine Haulesi Chiwaula; Diana L. Jere (AOSIS, 2022)
Background: An evidence based practice (EBP) research project was undertaken to implement EBP interventions utilising the Iowa model in order to build the capacity of the nurses in using research evidence to improve decision making and quality care. Aim: Exploring and understanding the experiences of nurse managers and practitioners who participated in the EBP change project. Setting: The study was conducted in the intensive care unit (ICU) of a tertiary hospital in Lilongwe district in Malawi. Methods: A qualitative approach and an exploratory-descriptive design was employed. The ICU was purposively selected as a unit where the EBP change project was implemented. A purposive sample of 10 nurse managers and practitioners was selected. Semi-structured interviews were conducted. All interviews were audio-recorded with a digital recorder and transcribed verbatim. Thematic analysis was applied to the transcripts. Results: The participants' experiences of implementing EBP interventions were underpinned by four themes namely, evidence-based patient management, effective nursing care, competence in delivering EBP, and factors interplaying in EBP. Use of model, protocol and availability of supportive managers and team were major determinants of EBP. Conclusion: It is recommended to continue utilising the Iowa Model to facilitate building the EBP capacities of providers during scale up. Contribution: Utilising the Iowa Model facilitates building of the capacity and empowers frontline nurses to effectively develop, implement and evaluate discipline specific EBP changes needed to improve practice and optimum care.